Building New Bridges Between Business and Society Recent Research and New Cases in CSR, Sustainability, Ethics and Governance (CSR, Sustainability, Ethics & Governance,, 2018)
This book provides a comprehensive understanding of the linkages between business and society by addressing key issues in corporate social responsibility (CSR), sustainability, ethics and governance. Thanks to the different visions and perspectives offered by a global group of authors with a broad range of expertise, the book offers a full spectrum of theoretical and practical approaches. Further, it combines the latest theoretical thinking with reviews of frameworks, cases and best practices from various industries and nations. In particular, the book offers a historical perspective on the origins of CSR and discusses CSR in relation to sustainability and management, with a special focus on CSR in Asia.